2018
DOI: 10.21873/cgp.20103
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Expression of CDK2AP1 in Human Breast Cancer: Correlation with Clinical and Pathological Parameters

Abstract: Background: Cyclin-dependent kinase 2associated protein 1 (CDK2AP1) interacts with CDK2AP2, modulates the actions of transforming growth factor-B1, cyclin-dependent kinase 2 and retinoblastoma protein, and closely interacts with micro-RNA21 and micro-RNA25. Our objective was to determine if CDK2AP1 mRNA expression levels were consistent with tumour-suppressive functions in breast cancer. Materials and Methods: A total of 134 samples were analysed. CDK2AP1 mRNA levels were measured using quantitative polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…For instance, Smad4 mRNA suppresses cell metastasis in prostate cancer [ 31 ]. CDK2AP1 mRNA acts as an anticancer gene in the progression of human breast cancer [ 32 ]. The mRNA expression of MITF has been detected to be upregulated in melanoma [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Smad4 mRNA suppresses cell metastasis in prostate cancer [ 31 ]. CDK2AP1 mRNA acts as an anticancer gene in the progression of human breast cancer [ 32 ]. The mRNA expression of MITF has been detected to be upregulated in melanoma [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…as a subunit of mitochondria, DAP3 is involved in the process of detachment from extracellular matrix-induced anoikis-induced apoptosis [ 33 ] and mediates IFN-induced apoptosis (interferon-γ), tumor necrosis factor receptor (TNF-α), Fas ligand (FasL) and TNF-related apoptosis-inducing ligand (TRAIL) to induce apoptosis [ 24 ]. Meanwhile, DAP3 is at the location of several important cellular pathways in tumorigenesis and has been shown to be expressed at elevated levels in aggressive glioblastoma cells and glioma cell lines with an induced migration phenotype [ 34 ]; survival analysis by Gera et al [ 35 ] in a clinical study of a cohort of 127 breast cancer patients showed higher survival rates in the highly transcribed group. Galactose lectin-3 (LGALS3, also known as galectin-3), a member of the galectin protein family, is one of the most widely studied galactose lectins in cancer and is involved in a variety of cellular activities including apoptosis, cell migration, proliferation, and angiogenesis [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, this significance was observed with PTEN and TP53 mutated samples. In breast cancer, Gera et al [ 15 ] reports that they found 39-fold increase of normalized mRNA expression of CDK2AP1 in noncancerous adjacent tissues [ 15 ]. Moreover, Xu et al [ 18 ] studied CDK2AP1 overexpression association with tumorigenesis in glioma in vitro and in vivo and found that, CDK2AP1 knockdown inhibits cells proliferation, and colony formation.…”
Section: Discussionmentioning
confidence: 99%
“…Varying levels of CDK2AP1 have been observed in tumors and adjacent non-cancerous normal tissues. Decreased expression has also been found in cancers such as breast [ 15 ], oral squamous cell carcinoma [ 16 ] and lung cancer [ 17 ]. On the contrary, a few studies reported high CDK2AP1 mRNA levels associate with tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation